2022
DOI: 10.3390/children9060783
|View full text |Cite
|
Sign up to set email alerts
|

Mental Well-Being during the COVID-19 Confinement among Adolescents in Catalonia: The Role of Demographic and Other COVID-Related Variables

Abstract: This study aimed to describe the impact of the COVID-19 pandemic on the social situation, self-perceived health status, and mental well-being of adolescents in Catalonia during home confinement, and to evaluate factors that are associated with poor overall mental well-being. An online cross-sectional study among a cohort of students (14–18 years old) of central Catalonia (DESKcohort) was performed during June–July 2020. Poisson regression models with robust variance were used to identify variables associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Poor family economic status was a significant risk factor for depression and PTG. In the study conducted by Folch et al [ 35 ], 57% of the participants ( n = 303, 14–18 years old) reported poor overall mental health, with females reporting worse mental health than males. Participants reporting a decrease in their family’s income were more likely to report poor overall well-being.…”
Section: Introductionmentioning
confidence: 99%
“…Poor family economic status was a significant risk factor for depression and PTG. In the study conducted by Folch et al [ 35 ], 57% of the participants ( n = 303, 14–18 years old) reported poor overall mental health, with females reporting worse mental health than males. Participants reporting a decrease in their family’s income were more likely to report poor overall well-being.…”
Section: Introductionmentioning
confidence: 99%